Cutaneous microcirculation in patients with peripheral arterial occlusive disease: Comparison of capillary blood circulation in the nail fold of finger and toe - Mrowietz, C.; Sievers, H.; Pindur, G.; Hiebl, B.; Jung, F. (Clinical hemorheology and microcirculation, 2020)
In patients with peripheral arterial occlusive disease (PAOD) a restricted circulation in cutaneous microvessels has been reported. In this study the velocity of erythrocytes (very) in finger nailfold capillaries - a vascular area without upstream macroangiopathy - and also in toe nailfold capillaries - a post-stenotic area –was investigated using capillary microscopy in apparently healthy subjects and patients with PAOD. Already in finger nailfold capillaries very of patients with PAOD under resting conditions was significantly lower than in capillaries of healthy subjects. This was also true for the circulation in toe capillaries. In addition, the erythrocyte velocities under resting conditions in the toe capillaries were significantly lower than in the finger capillaries. Similar results were found for the duration and the maximum velocity of postocclusive hyperemia. It is concluded that the resting blood flow in the skin microcirculation is impaired in PAOD patients, both under resting conditions and during postocclusive hyperemia in finger as well in toe nailfold capillaries.